2017
DOI: 10.1155/2017/2917925
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Nomograms for Survival and Metastases after Hysterectomy and Adjuvant Therapy in Uterine Cervical Cancer with Risk Factors

Abstract: Background. Three nomogram models for early stage uterine cervical cancer have been developed (KROG 13-03 for overall survival [OS], SNUH/AMC for disease-free survival [DFS], and KROG 12-08 for distant metastases-free survival [DMFS]) after radical hysterectomy (RH) and pelvic lymph node dissection (PLND). This study aimed to validate these models using our cohort with adjuvant radiotherapy. Methods. According to the eligibility criteria of nomogram studies, patients were enrolled in Group A (N = 109) for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Nomograms from multivariable logistic models are used as a graphical user interface to display the predicted probabilities of an event [19]. Nomograms are frequently used to estimate prognosis in oncology [20][21][22][23][24][25][26][27][28][29][30][31][32]. Gao et al developed a prognostic nomogram to assess the individual prognosis for CHB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms from multivariable logistic models are used as a graphical user interface to display the predicted probabilities of an event [19]. Nomograms are frequently used to estimate prognosis in oncology [20][21][22][23][24][25][26][27][28][29][30][31][32]. Gao et al developed a prognostic nomogram to assess the individual prognosis for CHB patients.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce this heterogeneity, several epidemiological, histological and treatment prognostic factors for recurrence and survival have been reported and are currently used to define optimal CC management [12] [13]. In this setting, different models have been developed based on the prognostic factors to predict recurrence and survival in LACC [6] [14][15] [16]. However, to date, few evidence-based data are available about patterns of recurrence (location, timing from initial treatment) and prognosis for FIGO stage IB2 to IIB CC.…”
Section: Introductionmentioning
confidence: 99%
“…A prognostic model is a formal combination, usually a statistical equation, of multiple predictors, from which risks of a specific outcome can be calculated for individuals (15)(16)(17). As for cervical cancer patients, due to the limited predictive value for the classification of the International Federation of Gynecology and Obstetrics (FIGO) alone, a couple of prognostic models have been proposed to predict and guide treatments based on different tumor and demographic characteristics (13,18). However, the uneven quality and the diversity of the clinical settings, outcomes, and predictors may limit the practicality of models, and systematic reviews on prognostic models of other diseases also suggested that the methodological features of existing studies varied (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%